PERANAN BP4KKP DALAM PENINGKATAN KETAHANAN PANGAN SEKTOR BERAS DI KABUPATEN INDRAGIRI HULU TAHUN 2010-2014 - ", Rickhy; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Symptoms of the highlights of this study is the low rice production area as well as food insecurity levels are high enough in Indragiri Hulu. Food security means food security conditions of both quantity and quality, safe, nutritious, diverse, equitable and affordable by the people's purchasing power. In addition to the threat of land conversion that continue to occur, the level of food insecurity is also due to the low price of rubber and palm oil have an impact on people's purchasing power. This study applies the theory of the role and implementation of policies with particular emphasis on programs conducted by BP4KKP in improving food security in Indragiri Hulu. Furthermore, this study used qualitative methods, implemented in particular in BP4KKP. The data obtained through the interview and literature study that supports extracting comprehensive information to further analyzed through descriptive analysis techniques. These results indicate that the Executive Agency of Agricultural Extension, Fisheries and Food Security Godhead (BP4KKP) in efforts to improve food security in the rice sector have carried out the planning and implementation of activities in accordance with the duties and functions given to BP4KKP. Despite the fact that efforts to increase food security in the rice sector faced constraints land conversion of agricultural land into plantations. The findings of subsequent studies is that the factors that affect BP4KKP in improving food security is the coordination does not go smoothly between the provincial government and district / city, the diversity of food and balanced nutrition for the consumption of the population Riau that still need to be improved, the prevalence of potential areas of food insecurity, lack of resources manpower and limited funds the implementation of activities.Keywords: Food Security, Roles, Policie